2012
DOI: 10.1586/ern.12.35
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual reminiscence therapy for people with dementia: systematic review

Abstract: This systematic review aims to review the potential psychosocial benefits of individual reminiscence therapy for people with dementia. Five randomized controlled trials were identified. All were carried out in nursing or care homes, and several different approaches were represented. The studies reported some immediate and longer-term psychosocial benefits to people with dementia of individual reminiscence work, where this involved a life review process or personalized, specific reminiscence work. These benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
154
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 28 publications
12
154
0
3
Order By: Relevance
“…Two further reviews of specific areas yielded firmer conclusions: That multicomponent behavioural interventions and bright light therapy for sleep led to improved sleep quality (Salami, Lyketsos & Rao, 2002) and that cognitive stimulation had cognitive and wider psychosocial benefits (Woods et al, 2012). Carrion et al's (2015) review found that cognitive interventions such as reality orientation had significant positive effects on cognitive functioning in six of the nine studies reviewed and two studies found a positive impact of cognitive interventions on depression.…”
Section: Table 3 About Herementioning
confidence: 99%
“…Two further reviews of specific areas yielded firmer conclusions: That multicomponent behavioural interventions and bright light therapy for sleep led to improved sleep quality (Salami, Lyketsos & Rao, 2002) and that cognitive stimulation had cognitive and wider psychosocial benefits (Woods et al, 2012). Carrion et al's (2015) review found that cognitive interventions such as reality orientation had significant positive effects on cognitive functioning in six of the nine studies reviewed and two studies found a positive impact of cognitive interventions on depression.…”
Section: Table 3 About Herementioning
confidence: 99%
“…With regard to the results obtained on autobiographical memory after reminiscence intervention and life review procedure, results suggest that people with dementia who attend reminiscence sessions improve their autobiographical memory [85,99,100], being observed improvements in recalling both facts and events, that is, in semantic memory and episodic memory.…”
Section: Reminiscence Therapymentioning
confidence: 97%
“…Literature describes the privileged role of non-pharmacological interventions in multidimensional models, by integrating the cognitive, functional, behavioral, and affective dimensions. In fact, the significant impact, effectiveness, and health gains obtained through the implementation of structured reminiscence therapy (RT) programs in older people with cognitive impairment are particularly relevant, namely decreased disorientation and depression, and improved well-being and cognitive function (Bohlmeijer, Roemer, Cuijpers, & Smit, 2007;Subramaniam & Woods, 2012;Webster, Bolhmeijer, & Westerhof, 2010). Evidence shows that RT is an important therapeutic strategy for the empowerment of people with NCDs, providing moments of pleasure with dignity and a purpose in life.…”
Section: Introductionmentioning
confidence: 99%
“…RT is a cognitive stimulation technique used to recall old memories with the purpose of triggering past experiences. To this end, RT uses old materials (newspapers, household utensils, photos, songs) to stimulate memory and allow them to share and value their experiences (Subramaniam & Woods, 2012;Webster et al, 2010). At an international level, the process of development and validation of RT programs used in controlled studies is not always clearly described, which is a potential methodological limitation that may explain the inconsistent results found in different studies on the effectiveness of RT programs (Bohlmeijer et al, 2007;Cotelli, Manenti, & Zanetti, 2012;Stinson, 2009).…”
Section: Introductionmentioning
confidence: 99%